The Ghost Fields : Ruth Galloway #7 - Griffiths, Elly (Boston : Houghton Mifflin Harcourt, 2015)
The unsettling discovery of a downed World War II plane with a body inside inside leads forensic archaeologist Ruth Galloway and DCI Nelson to uncover a wealthy family's secrets.
Keywords: Galloway, Ruth (Fictitious character) -- Fiction; Women forensic anthropologists -- Fiction; Murder -- Investigation -- Fiction; Galloway, Ruth (Fictional character) -- Fiction; Women forensic anthropologists -- Fiction; Homicide -- Fiction; Criminal investigation -- Fiction; Norfolk (England) -- Fiction; Norfolk (England) -- Fiction; Mystery fiction